2013
DOI: 10.4161/gmic.25583
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammation and oxidative stress

Abstract: Helicobacter pylori is the leading risk factor associated with gastric carcinogenesis. H. pylori leads to chronic inflammation because of the failure of the host to eradicate the infection. Chronic inflammation leads to oxidative stress, deriving from immune cells and from within gastric epithelial cells. This is a main contributor to DNA damage, apoptosis and neoplastic transformation. Both pathogen and host factors directly contribute to oxidative stress, including H. pylori virulence factors, and pathways i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 59 publications
0
65
0
Order By: Relevance
“…Despite substantial increases in the ability of the high risk versus low risk strains to induce SMOX, oxidative stress, and DNA damage, these affects were not attributable to differences in their EPIYA motifs or the translocation and phosphorylation of CagA, which are linked to carcinogenesis. 19,21,28,35 We have reported that in response to North American H. pylori clinical isolates, the induction of SMOX expression in gastric epithelial cells was greater in strains that expressed CagA. 27 In the current study, the effect of cagA deletion in different strains on SMOX expression in gastric epithelial cells was only partial.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Despite substantial increases in the ability of the high risk versus low risk strains to induce SMOX, oxidative stress, and DNA damage, these affects were not attributable to differences in their EPIYA motifs or the translocation and phosphorylation of CagA, which are linked to carcinogenesis. 19,21,28,35 We have reported that in response to North American H. pylori clinical isolates, the induction of SMOX expression in gastric epithelial cells was greater in strains that expressed CagA. 27 In the current study, the effect of cagA deletion in different strains on SMOX expression in gastric epithelial cells was only partial.…”
Section: Discussionmentioning
confidence: 49%
“…19–22 CagA has been implicated in H. pylori -induced apoptosis, proliferation, oxidative stress, and DNA damage in gastric epithelial cells. 19,28,39 In the present study, all H. pylori clinical strains used in our cell culture models were positive for cagA , and for the vacA s1m1 allele, so we excluded potential differences in these virulence genes. Despite substantial increases in the ability of the high risk versus low risk strains to induce SMOX, oxidative stress, and DNA damage, these affects were not attributable to differences in their EPIYA motifs or the translocation and phosphorylation of CagA, which are linked to carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that more than 50 % of the human population is infected with H. pylori , leading to chronic gastritis and peptic ulcer disease (Cover and Blaser 2009; Sibony and Jones 2012). Importantly, H. pylori is the greatest risk factor for the development of gastric adenocarcinoma, the third leading cause of cancer deaths worldwide (Bonequi et al 2013; Hardbower et al 2013, 2014; Nomura et al 1991; Parsonnet et al 1991; Peek and Blaser 2002; Ferlay et al 2015). The global prevalence of infection and the high degree of gastric cancer mortality clearly indicate that H. pylori is a significant public health issue.…”
Section: Introductionmentioning
confidence: 99%
“…H. pylori infection induces both innate and adaptive immune responses, but these responses are inadequate to clear the infection and result in pro-carcinogenic, chronic inflammation (Hardbower et al 2013, 2014; Peek et al 2010; Robinson et al 2007; Wilson and Crabtree 2007). Macrophages represent a dynamic subset of innate immune cells and serve to coordinate the immune response to H. pylori (Murray and Wynn 2011; Peek et al 2010; Robinson et al 2007; Wilson and Crabtree 2007).…”
Section: Introductionmentioning
confidence: 99%